Analisis Strategi Pemasaran Syariah dalam Menarik Minat Beli Masyarakat di Toko Kue Shinta Bakery Simpang III Sipin Jambi - Dinda, Dinda; Hafiz, Ahsan Putra; Saputra, Jevi (ARZUSIN, 2024)
This study aims to determine whether the strategy carried out by the Shinta Bakery cake shop is going well or not and to find out how marketing strategies affect consumer behavior in buying cakes at the shinta bakery shop. This type of research is descriptive qualitative, which describes an event that has occurred or existing cases that provide a clear picture of the problem to be studied. The objects used in conducting this research are the community, employees and owners at the Shinta Bakery cake shop. The types of data used in this research include primary and secondary data. The methods used to collect data for this research are observation, interviews and documentation. Based on the discussion, it can be concluded as follows. First, In terms of Islamic Marketing Strategy, Toko Shinta Bakery has been in accordance with applying the concept of sharia marketing strategy, namely product, price, promotion, place. As well as applying the characteristics of Islamic marketing, namely Rabbaniyah, Akhlaqiah, Al-Waqiyah, Insaniyah. Second, the advantages and disadvantages of implementing sharia marketing strategies in Toko Shinta Bakery are, the advantages are selling products at affordable prices and good quality, the disadvantages are not managing their gofood franchise properly, lack of parking lots, and rarely giving discounts.